Can We Speak of Global Feminism? - Bt Mamma, Beche (Journal of International and Local Studies, 2017)
This paper attempts to answer the question whether globalization that blurs the state’s boundaries can unite feminist movement to be a global feminism. The goal is to eliminate all the differences and diversities that obstruct women in the West and women in the South, such as the wealth issue, the western women perspective, the commonality and the colonialism in the third/ south/ countries. Used post-colonialism feminism approach, this paper argues the attempt to unite all the differences and diversities that lie between women in the West and women in the South obstructed by the sharp of live differentiations and history that influenced them.